Searching for the New World Monetary Standard - Ishkhanov Aleksandr Vladimirovich (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 3, Èkonomika,Èkologiâ, 2014)
In the article the influence of the existing world currency system on the international financial relations is considered, the retrospective analysis of the existing four currency systems is carried out. The change of a world currency order is justified. The concept of the new international currency standard based on division of functions of money between separate financial instruments of one currency is offered. The functional communications between financial instruments are revealed. The comparison of function of money and independent tools of new world currency is carried out, it is supposed that tools are actually completely capable to carry out all functions of money. Therefore, the new international currency standard is based on division of these functions between separate tools and can be defined as polytool. The general function chart of the polytool world currency standard including their functional connections between reserve tool, reverse tool and credit as well as their characteristics which should determine the activity of world reserve system. Prerequisites of replacement of the Jamaican currency system by the alternative are proved; the most perspective way of transition to the polytool standard is revealed; the additional functions of the polytool standard are designated – stimulation of issuers of the leading world currencies to refuse harmful policy of competitive devaluation, stimulation of integration of the countries and creation of collective currencies (currency zones and associations) that will significantly increase financial stability of world economy.